2012
DOI: 10.1080/13675567.2012.745840
|View full text |Cite
|
Sign up to set email alerts
|

Process redesign for effective use of product quality information in meat chains

Abstract: To fulfil segmented consumer demand and add value meat processors seek to exploit quality differences in meat products. Availability of product quality information is of key importance for this. We present a case study where an innovative sensor technology that provides estimates of an important meat quality feature is considered. Process design scenarios that differ with respect to sorting complexity, available product quality information, and use of temporary buffers are assessed using a discrete event simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Transparency in red meat supply chains also benefit from benchmarking techniques (Manning et al, 2008). Recent developments in information and communications technology and sensing technology facilitate the means to gather, communicate, and process product quality information (Rijpkema et al, 2012). But in the present study it was found that there is no IT tool that can track the product from initial stage to final delivery stage.…”
mentioning
confidence: 59%
“…Transparency in red meat supply chains also benefit from benchmarking techniques (Manning et al, 2008). Recent developments in information and communications technology and sensing technology facilitate the means to gather, communicate, and process product quality information (Rijpkema et al, 2012). But in the present study it was found that there is no IT tool that can track the product from initial stage to final delivery stage.…”
mentioning
confidence: 59%
“…In SC coordination, information and communication technology (ICT) enables information sharing among actors. ICT allows increasing the productivity and competitiveness performances within the SC (Rijpkema, 2012). ICT supports the integration of production and distribution processes, management of information flows, quality, traceability, food safety, flow management, logistics management and increasing sustainability.…”
Section: Agri-food Supply Chain Optimization Conceptual Modelmentioning
confidence: 99%
“…ICT supports the integration of production and distribution processes, management of information flows, quality, traceability, food safety, flow management, logistics management and increasing sustainability. In addition ICT systems allows the transfer of the knowledge (technology in agricultural and agro-industrial processes) to operators, thus constituting a support mechanism for policy makers for the implementation of training and training activities in line with company operations (Rijpkema, 2012).…”
Section: Agri-food Supply Chain Optimization Conceptual Modelmentioning
confidence: 99%
“…The resulting model can be a useful tool for deciding on the interventions to implement in a given context with respect to the desired PHL reduction. Examples of previous researches that used simulation modelling in fresh produce chains include studies by van der Vorst et al (2007) and Rijpkema et al (2012).…”
Section: Limitations and Recommendations For Further Researchmentioning
confidence: 99%